Análisis de la microestructura de sueño en pacientes con insomnio idiopático - Arana Lechuga, Débora Yoaly (Universidad Autónoma Metropolitana, 2012)
The main purpose of this research was to describe electroencephalographic activity during sleep and the cyclical alternating pattern (CAP) in patients with idiopathic insomnia. It included 22 patients (8 male, 14 female) with a diagnosis of idiopathic insomnia, ranging in age from 19 to 45 years old, the average being 30, who were recently diagnosed and without prior treatment. Sleep studies were performed with the international 10-20 system and bipolar montages (32 electrodes with 16 derivations), record of the electrooculogram, electromyography, electrocardiogram, chest/abdominal respiratory movements, nasal flow and oximetry. Of the 22 patients registered, 10 patients, who represented 45% of the sample, did not present with any abnormal activity in the analysis of the cerebral electrical activity, while the remaining 12 patients (55%) presented with irritative activity (spikes, acute waves in phase inversion and outbreaks of slow activity) in the electroencephalographic record. The abnormal activity presented only in the left hemisphere in 66% of the patients. It presented in both hemispheres for the remaining 33%. With regard to the sleep record, significant differences were found between the groups (patients with alterations in the EEG vs. patients without alterations) in sleep latency, total sleep time, total wake time, light sleep percentage, slow waves percentage and in the A1 sub-type index of the cyclical alternating pattern. These findings suggest that within the population of patients with idiopathic insomnia, there is a sub-group whose symptoms are more severe and whose sleep complaints (insomnia) could be closely related to the electroencephalographic findings present during sleep.; El objetivo principal de esta investigación fue describir la actividad electroencefalográfica durante el sueño y el patrón alternante cíclico (CAP) en pacientes con insomnio idiopático. Se incluyeron 22 pacientes (8 masculinos, 14 femeninos) con diagnóstico de insomnio idiopático con rango de edad de 19 a 45 años y promedio de 30 años, de recién diagnostico y sin tratamiento previo. Se realizaron estudios polisomnográficos con el montaje internacional 10-20 y referencias bi-polares (32 electrodos con 16 derivaciones), registro del electrooculograma, electromiograma, electrocardiograma, movimientos respiratorios tóraco-abdominal, flujo nasal y oximetría. De los 22 pacientes registrados 10, que representan el 45% de la muestra, no presentaron actividad anormal en el análisis de la actividad eléctrica cerebral; mientras que los 12 pacientes restantes (55%) presentaron actividad irritativa (puntas, ondas agudas en inversión de fase y brotes de actividad lenta) en el registro electroencefalográfico. La actividad anormal se presentó únicamente en hemisferio izquierdo en el 66% de los pacientes. En el 33% restante se presentó en ambos hemisferios. En relación a los estudios polisomnográficos se encontraron diferencias significativas entre grupos (pacientes con alteración en el EEG vs pacientes sin ella) en la latencia a sueño, tiempo total de sueño, tiempo total de vigilia, eficiencia de sueño, porcentaje de sueño ligero, porcentaje de sueño de ondas lentas y en el índice del subtipo A1 del patrón alternante cíclico. Estos hallazgos sugieren que dentro de la población de pacientes con insomnio idiopático, existe un sub-grupo cuyos síntomas son más severos y la queja de sueño (insomnio) podría estar asociada íntimamente a los hallazgos electroencefalográficos presentes durante el sueño.